Social cost-benefit analysis of regulatory policies to reduce alcohol use in The Netherlands. (13th November 2019) - de Wit, G A; van Gils, P F; Over, E A B; Suijkerbuijk, A W M; Lokkerbol, J; Smit, F; Spit, W J; Evers, S M A A; de Kinderen, R J A
Abstract: Background: If all costs and all benefits of alcohol use are expressed in monetary terms, the net costs were 2, 3 to 4, 2 billion euro in 2013. Examples of the costs of alcohol are less productivity at work, costs of police and justice and traffic accidents. Methods: In this study three regulatory policies have been modelled using the Social Cost-Benefit Analysis (SCBA) approach. Regulatory policies aimed at curbing alcohol consumption were (1) an increase in excise taxes, (2) a reduction of the number of sales venues, and (3) a total mediaban for advertising alcohol. Results: In the long run, over a period of 50 years, an increase in excise taxes of 50% will result in societal benefits of 4.5 to 10.7 billion euro, an increase of excise taxes of 200% will result in societal benefits of 12.2 to 35.8 billion euro. The societal benefits of closure of 10% of sales venues are estimated at 1.8 to 4.3 billion euro after 50 years, and at 4.6 to 10.7 billion euro when 25% of sales venues would be closed. The societal benefits of a mediaban would amount to 3.5 to 7.8 billion euro after 50 years, but this estimate is surrounded by uncertainty. Conclusions: Regulatory policies aimed at reducing the amount of alcohol consumed, such as a further increase of excise taxes, a reduction of the number of sales venues and a total mediaban, will result in savings for society at large. However, costs and benefits are spread unequally over the different stakeholders.